THE EFFECT OF TEACHER'S WORKLOAD AND MOTIVATION ON TEACHER'S WORK PERFORMANCE IN SMK NEGERI 1 RANTAU UTARA - Sihat Ridwanto; Zainuddin Zainuddin; Anton Sinaga (JURNAL PROINTEGRITA, 2019)
The purpose of this study is to find out (1) whether there is an influence of teacher workload and teacher work motivation in a parse manner on teacher performance at SMK Negeri 1 Rantau Utara, (2) whether there is an influence of teacher workload and teacher work motivation simultaneously on student achievement in SMK Negeri 1 Rantau Utara. The technique of sampling in this study was total sampling with total 44 respondents. Data collection techniques using questionnaires, before the questionnaire was distributed first carried out trial analysis, namely test validity and reliability. Hypothesis testing is done by using multiple linear regression tests. Partially, the results of this study are tcount X12> ttable = 1.68 and the probability value (0.000) <0.05 means that partially the teacher's workload and teacher work motivation significantly influence teacher performance. Simultaneously, the results of this study are Fcount X12> Ftable = 21,050 and probability values (0,000) <0.05 means that simultaneously the teacher's workload and teacher's work motivation significantly influence teacher performance. Based on the test results of the R2 coefficient of determination, it is known that Adjusted R Square found that teacher workload and teacher work motivation simultaneously on teacher performance in SMK Negeri 1 Rantau Utara amounted to 48.30%.